ChemInform Abstract: A Concise Synthesis of Mupirocin H Using a Cross‐Metathesis‐Based Strategy. Issue 10 (March 2015) - Sengupta, Sandip; Sim, Taebo
Abstract The target compound is synthesized in 17 steps and 10.1% overall yield starting from (+)‐Roche ester.